Pengaruh Pertumbuhan Penjualan, Profitabilitas, Struktur Aktiva, dan Likuiditas Terhadap Struktur Modal Pada Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar di BEI - Vovi Pramudita; Fitriasuri Fitriasuri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the effect of sales growth, profitability, asset structure and liquidity on capital structure which is proxied by the Debt to Equity Ratio with a population covering all food and beverage sub-sectors. Companies listed on the Indonesia Stock Exchange during the observation period, namely 2019-2023. Of all the food and beverage companies listed on the IDX, we selected 12 companies using a purposive sampling technique. Then to determine the effect of the independent variables on the dependent variable, all secondary data is processed according to the indicators used and multiple linear regression analysis is performed. The results of this study indicate that profitability (ROA) and liquidity have an effect on capital structure (DER) based on the significance value of the t test of 0.001 or less than 0.05 and 0.17 or less than 0.05. Thus, the hypothesis that profitability and liquidity affect the capital structure can be accepted. While the variable sales growth and asset structure have no effect on capital structure (DER) because the significance level of the t test is 0.225 and 0.965 or greater than 0.05. Therefore, the hypothesis that profitability and liquidity affect capital structure (DER) is unacceptable.